Immunogenicity and Reactogenicity of 13-Valent Pneumococcal Conjugate Vaccine Among Infants, Toddlers, and Children in Western Burkina Faso: Results From a Clinical Trial of Alternative Immunization Schedules. (8th October 2018) - Moïsi, Jennifer C; Yaro, Seydou; Kroman, Sita S; Gouem, Clarisse; Bayane, Dramane; Ganama, Seydou; Meda, Bertrand; Nacro, Boubacar; Njanpop-Lafourcade, Berthe-Marie; Ouangraoua, Soumeya; Ouedraogo, Issaka; Sakande, Souleymane; et al.
Abstract: Background: Many African countries have introduced pneumococcal conjugate vaccine (PCV) into their routine immunization program to reduce the burden of morbidity and death that results from Streptococcus pneumoniae infection, yet immunogenicity and reactogenicity data from the region are limited for the 2 available PCV products. Methods: We conducted a randomized trial of 13-valent PCV (PCV13) in Bobo-Dioulasso, Burkina Faso. Infants received 3 doses of PCV at 6, 10, and 14 weeks of age or at 6 weeks, 14 weeks, and 9 months of age; toddlers received 2 doses 2 months apart or 1 dose beginning at 12 to 15 months of age; and children received 1 dose between 2 and 4 years of age. We measured each participant's serotype-specific serum immunoglobulin G concentration and opsonophagocytic activity before and after vaccination. For each age group, we compared immune responses between study arms and between the standard schedule in our study and the PCV13-licensing trials. Results: In total, 280 infants, 302 toddlers, and 81 children were assigned randomly and underwent vaccination; 268, 235, and 77 of them completed follow-up, respectively. PCV13 resulted in low reactogenicity in all the study arms. The vaccine elicited a strong primary immune response in infants after 2 or more doses and in children aged 1 to 4 years after 1 dose. Infants who received a booster dose exhibited a robust memory response. Immunogenicity was higher than or comparable to that observed in the PCV13-licensing trials for a majority of serotypes in all 3 age groups. Conclusions: PCV13 has a satisfactory immunogenicity and reactogenicity profile in this population. Our findings will help support decision making by countries regarding their infant and catch-up vaccination schedules. Abstract : PCV13 has a satisfactory reactogenicity and immunogenicity profile when administered to infants, toddlers, and children according to alternative immunization schedules in Burkina Faso.